2017
DOI: 10.1016/j.colsurfa.2016.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonated methyl esters, linear alkylbenzene sulfonates and their mixed solutions: Micellization and effect of Ca2+ ions

Abstract: Here, we compare the properties of sulfonated methyl esters of fatty acids (SME) and linear alkylbenzene sulfonate (LAS) with respect to the effect of calcium ions on their surface tension and the effect of their mixing on the critical micelle concentration (CMC). The theoretical interpretation of surface tension isotherms obtained in the presence of NaCl and CaCl 2 allowed us to determine the parameters that characterize the surfactant adsorption layers and counterion binding. The excluded area per molecule i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…The addition of 5 mM Ca 2+ decreases σ AW with 1–2 mN m −1 . The effect is stronger for SLES as compared to C16‐SME, in agreement with the finding for relatively low binding energy of the Ca 2+ ions to the sulfonate groups of SME (Ivanova et al, ). The lowering of σ AW with 7–9 mN m −1 due to DDAO is a much stronger effect than that of 5 mM Ca 2+ .…”
Section: Experimental Characterization Of the Studied Systemssupporting
confidence: 90%
See 2 more Smart Citations
“…The addition of 5 mM Ca 2+ decreases σ AW with 1–2 mN m −1 . The effect is stronger for SLES as compared to C16‐SME, in agreement with the finding for relatively low binding energy of the Ca 2+ ions to the sulfonate groups of SME (Ivanova et al, ). The lowering of σ AW with 7–9 mN m −1 due to DDAO is a much stronger effect than that of 5 mM Ca 2+ .…”
Section: Experimental Characterization Of the Studied Systemssupporting
confidence: 90%
“…SME are derived from renewable sources and are considered as a green alternative of petroleum‐derived surfactants (Jin et al, ; Lim et al, , ; Maurad et al, ; Siwayanan et al, ; Xu et al, ). SME are insensitive to the water hardness, unlike the linear alkylbenzene sulfonates (LAS), which are widely used in cleaning formulations (Cohen and Trujillo, ; Ivanova et al, ; Lim et al, , ; Xu et al, ). Mixtures of SME and LAS have been shown to improve the LAS solubility in hard water and have been used to achieve significant builder's reduction in detergent formulations (Lim et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, they will be denoted C n SME, n = 12, 14, 16, 18. Information for the adsorption and micellar properties of C n SME can be found in Refs. [70][71][72]. So far, there is a single study on the rheology of micellar SME solutions without cosurfactants (like CAPB) and thickeners, but in the presence of nanoparticles [73].…”
Section: Introductionmentioning
confidence: 99%
“…A previous foamability and Krafft temperature study has shown that α‐MES has excellent tolerance toward water hardness (Lim et al, ). To better understand the tolerance of α‐MES to hard water, Ivanova et al characterized the binding energy of Ca 2+ ions to the headgroups of α‐MES by means of theoretical modeling (Ivanova et al, ). The study showed that the binding energy of the Ca 2+ ions (2.39 К T) to the headgroup of α‐MES is smaller than that of Na + (2.91 К T), which helps explain the superiority of α‐MES under challenging conditions.…”
Section: Introductionmentioning
confidence: 99%